Variable residual activity of K-Othrine® PolyZone and Actellic® 300 CS in semi-field and natural conditions in the Democratic Republic of the Congo - Leonard M. Ngwej; Emmanuel M. Mashat; Clarence K. Mukeng; Henri T. Mundongo; Françoise K. Malonga; Jean-Christophe K. Kashala; Michael J. Bangs (Malaria Journal, 2021)
Abstract Background Indoor Residual Spray (IRS) against vector mosquitoes is a primary means for combating malaria transmission. To combat increased patterns of resistance to chemicals against mosquito vectors, alternative candidate insecticide formulations should be screened. With mortality as the primary endpoint, the persistence of residual efficacy of a polymer-enhanced pyrethroid suspension concentrate containing deltamethrin (K-Othrine® PolyZone—KOPZ) applied at 25 mg active ingredient (ai)/m2 was compared with a microencapsulated organophosphate suspension formulation of pirimiphos-methyl (Actellic® 300CS—ACS) applied at 1 g ai/m2. Methods Following standard spray application, periodic contact bioassays were conducted for at least 38 weeks on four types of wall surfaces (unbaked clay, baked clay, cement, and painted cement) sprayed with either KOPZ or ACS in simulated semi-field conditions. Similarly, two types of existing walls in occupied houses (painted cement and baked clay) were sprayed and examined. A colonized strain of female Anopheles arabiensis mosquitoes were exposed to treated or untreated surfaces (controls) for 30 min. For each wall surface test period, 40 treatment mosquitoes (4 cones × 10) in semi-field and 90 (9 cones × 10) in ‘natural’ house conditions were used per wall. 30 mosquitoes (3 cones × 10) on a matching unsprayed surface served as the control. Insecticide, wall material, and sprayed location on wall (in houses) were compared by final mortality at 24 h. Results Insecticide, wall material, and sprayed location on wall surface produced significant difference for mean final mortality over time. In semi-field conditions, KOPZ produced a 72% mean mortality over a 38-week period, while ACS gave 65% (p < 0.001). Painted cement wall performed better than other wall surfaces throughout the study period (73% mean mortality). In the two occupied houses, KOPZ provided a mean mortality of 88%, significantly higher than ACS (p < 0.001). KOPZ provided an effective residual life (≥ 80% ...